محمد بن عبدالرسول بن عبدالسيد العلوي الحسيني: سيرته وآثاره - إبراهيم، ياسر نجاح عبدالحميد (جامعة المنيا - كلية دار العلوم, 2022)
مما لا شك فيه أن الحركة العلمية والفكرية في كل الأقطار وفي مختلف الأزمنة تتأثر بالظروف السياسية، والاقتصادية والاجتماعية، ويظهر ذلك خاصة في غزارة أو ندرة الإنتاج الفكري، مداً وجزراً تبعاً لهذه الظروف في مجالات المعرفة وحقولها المبحوث فيها والمثيرة للاهتمام. وقيمة المعرفة والإبداع المنتج في كل مرحلة إنما تقاس بقدرته على حل إشكالات العصر وتلبية حاجات الناس، لا سيما في القضايا الملحة والنوازل الملمة. يضاف إلى ذلك أن خصوصية المعرفة الشرعية تقتضي الاجتهاد في ضوء مقاصد الشريعة. وغاية هذا البحث اختصار أهم الأحداث السياسية التي أرخت بظلالها على البيئة الاقتصادية والاجتماعية في القرن الحادي عشر الهجري، وإبراز انعكاساتها على الإبداعات الفكرية والمعرفية في هذه المرحلة، باعتماد مصادر مختلفة في مقدمتها كتب النوازل الفقهية والرحلات والإجازات والفهارس إلى جانب كتب التاريخ العام التي اهتمت بالتأريخ للمرحلة. ومن هنا كان عصر المؤلف امتداد لعقود وقرون متتالية سبقته من التمزق والحروب الداخلية، على امتداد رقعة الأمة الإسلامية من الصين شرقا وإلي المغرب الأقصى والأندلس غربا، وذلك بعد سقوط الخلافة العباسية في بغداد إثر احتلالها من قبل المغول، لذا اتسم عصر المؤلف عامة بالضعف، والانقسام المذهبي والسياسي، وكثرة القلاقل والفتن، وهذا ما أشار إليه الطورى في مقدمته بقوله:- (فهذا زمان قلت فيه البركات، وكثرت فيه الشرور والآفات، وتكدرت النعما بعد الصفا، وتظاهرت المنكرات، وفقد من يعيد الهارب، وعز من يلوذ به الطالب، وملأت الشحنا القلوب، ودارت رحا الحرب، ودهمت الأنام، وأحاطت بالناس الخطئة والآثام، وانتشر شر المارقين، وعيل صبر المتقين وانقطعت سبل المسالك، وترادفت الفتن والمهالك، ومنع الخلاص ولات حين مناص والأمر لا يزداد إلا شدة، وصار العالم مؤخرا، والجاهل مقدما مصدرا) عاش المؤلف في عصر الدولة العثمانية وكانت الحياة الاجتماعية في ذلك العصر ليس للنسب والعائلة والانتماء العنصري دور مهم باستثناء اختيار السلطان ولكنه كان قائما على الوضع الوظيفي وقد قسم بعض الباحثين المجتمع العثماني إلى صنفين -الصنف الأول:- الصنف العسكري وهي تشمل فئات متباينة في المواقع والدرجات الاجتماعية، وتمتد من السلطان في ذروة الهرم الاجتماعي إلى خادم المسجد الذي يعمل أجيرا في وقف من الأوقاف، فهذا المفهوم لهذا الصنف تعدي الجند إلى دائرة واسعة تشمل المكلفين بالخدمة العامة، بل حاز منسوبو الطبقة العلمية على الصفة العسكرية حتي من غير تعيين في وظيفة، مثل: القضاة والمدرسين، وطلاب المدارس الدينية العليا، والمجازين فيها، كذلك يلحق بهم فئات أسقطت عنهم الضرائب كلها أو قسم منها من غير خدمة يخدمون بها الدولة وهم: الشيوخ الزوايا، والأشراف. وتتمتع فئات هذه الطبقة بامتيازات عديدة تميزها عن الرعية وخصوصا في الضرائب، فهي تتمتع بالإعفاء من رسوم الرعية الملزمة، ويعد هذا الإعفاء معيارا لتمييز الصنف العسكري عن الرعية في تشكيلات الدولة العثمانية. ويمكن أن نقسم فئات هذه الطبقة إلى ثلاث فئات:- الفئة الأولى: السلاطين، فقد كانت معيشتهم سببا في النتائج السيئة على الدولة، وعلى أفراد المجتمع ككل. وقد كانت حياة بعض الخلفاء العثمانيين في هذه الفترة تتسم بالبذخ والترف، ظهر ذلك في المباني والقصور الفخمة التي تفننوا في بنائها، كما انساق كثير من هؤلاء وراء رغبات نسائهم وأمهاتهم، وقد أدى هذا إلى فوضى داخل الدولة، وإلي تفشي الظلم وانتشار الرشاوى والتمرد على السلطان. There is no doubt that the scientific and intellectual movement in all countries and at different times is affected by political, economic and social conditions. The value of knowledge and creativity produced at each stage is measured by its ability to solve the problems of the times and meet the needs of people, especially in urgent issues and painful calamities. In addition, the specificity of legal knowledge requires diligence in the light of the purposes of Sharia. The purpose of this research is to summarize the most important political events that cast their shadow on the economic and social environment in the eleventh century AH, and to highlight their repercussions on the intellectual and cognitive innovations at this stage, by adopting various sources, foremost of which are jurisprudential calamities, trips, vacations and indexes, as well as general history books that were concerned with the history of the stage.. Hence, the author’s era was an extension of successive decades and centuries that preceded it of fragmentation and internal wars, along the Islamic nation from China in the east and to the Far Maghreb and Andalusia in the west, after the fall of the Abbasid Caliphate in Baghdad following its occupation by the Mongols, so the author’s era was generally characterized by weakness and division. Doctrinal and political, and a lot of unrest and strife, and this is what Al-Toori referred to in his introduction by saying: “This is a time in which blessings were few, and evils and afflictions multiplied, and blessings became plentiful after purity, and evils manifested, and those who returned the fugitive were lost, and the honor of the seeker sought refuge, and the consignments were filled with Hearts, wars raged, peoples invaded, sins and misdeeds surrounded people, the evil of renegades spread, the patience of the pious, the paths were cut off, temptations and perils were intertwined, salvation was prevented, and the matter only increased in severity, and the world became recently, and the ignorant in advance was a source. The author lived in the era of the Ottoman Empire, and social life in that era did not have an important role for descent, family and racial affiliation, except for the choice of the Sultan, but it was based on the job situation. Some researchers divided the Ottoman society into two types The first category: The military category, which includes different categories in positions and social ranks, and extends from the sultan at the height of the social hierarchy to the servant of the mosque who works as a wage-earner in an endowment. Members of the scientific class have military status, even without being appointed to a job, such as: judges, teachers, students of high religious schools, and those who are licensed in them. They are also joined by groups for whom all or part of the taxes have been dropped without serving the state, and they are: The sheikhs, the corners, and the supervisors.. The categories of this class enjoy many privileges that distinguish them from the parish, especially in taxes. They enjoy exemption from binding parish fees, and this exemption is a criterion for distinguishing the military class from the parish in the formations of the Ottoman Empire. The classes of this class can be divided into three classes: The first category: the sultans, for their livelihood was a cause of bad consequences for the state, and for the members of society as a whole. The life of some of the Ottoman caliphs in this period was characterized by extravagance and luxury, this appeared in the luxurious buildings and palaces that they built, as many of these went behind The desires of their women and their mothers, and this led to chaos within the state, to the spread of injustice, the spread of bribery, and rebellion against the Sultan.
Keywords: الحسيني، محمد بن عبدالرسول، ت. 1103 هـ. -- السيرة الذاتية -- العلماء المسلمون -- التاريخ الإسلامي